Semi-LASER 1H MR spectroscopy at 7 Tesla in human brain: Metabolite quantification incorporating subject-specific macromolecule removal - Penner, Jacob; Bartha, Robert (Magnetic resonance in medicine, 2015)
Purpose To develop an in vivo 1H short‐echo‐time semi‐LASER spectroscopy protocol at 7 Tesla (T) incorporating subject‐specific macromolecule removal. Methods T1 constants of the major metabolites were measured with little macromolecule contribution in seven healthy volunteers and used to optimize double inversion metabolite nulling. Spectra were acquired from parietal–occipital cortex of five healthy volunteers. Metabolite‐nulled macromolecule spectra were subtracted from the metabolite spectra before fitting in the time domain with prior‐knowledge templates. Absolute metabolite concentrations were determined by referencing to the water signal, following partial volume and relaxation corrections. Results The average signal to noise ratio, N‐acetylaspartate peak height divided by the baseline noise standard deviation, was 48 ± 6. T1 constants for N‐acetylaspartate, glutamate, creatine, and choline were 1.71 ± 0.15 s, 1.68 ± 0.19 s, 1.63 ± 0.10 s, and 1.41 ± 0.09 s, respectively. The optimal double inversion times for metabolite suppression were TI1 = 2.09 s and TI2 = 0.52 s. The coefficient of variation was less than 10% for N‐acetylaspartate, creatine, choline, and myo‐inositol, and less than 20% for glutamate and glutamine. Conclusion Short echo‐time 1H semi‐LASER spectroscopy at 7T incorporating subject‐specific macromolecule removal yielded reproducible brain metabolite concentrations ideal for applications in disease conditions where macromolecule contributions may deviate from the norm. Magn Reson Med 74:4–12, 2015. © 2014 Wiley Periodicals, Inc.